GENESIS OF THE TERM "TEACHING METHODS" WITHIN THEORY OF EDUCATION - Svetlana Skvortsova (Erudio Journal of Educational Innovation, 2018)
The article presents analysis of the term «teaching methods» in Russian and foreign theory of education. A thorough reading from the works of Russian and British papers on the theory of education has been performed, various kinds of interpreting the term «teaching methods» have been revealed, comparison of Russian and Foreign ways of interpreting the term is presented.